Ansiolitic effect of the ethanolic extract of the leaves of Citrus aurantium L. on Mus musculus (Research, Society and Development, 2023)
The aim of this study was to evaluate the possible anxiolytic effect of the ethanolic extract of Citrus aurantium L. leaves on experimental models sensitive to anxiolytic drugs. The mice were divided into three groups (test, positive control, negative control) for administration of the ethanolic extract of Citrus aurantium L. leaves, diazepam and vehicle. To assess motor activity in mice (spontaneous activity), the Open Field and Hide the Spheres tests were carried out. The experimental values obtained are expressed as mean ± standard error of the mean (SEM) and statistical analysis was carried out using the Kruskal-Wallis test, followed by Dunn's multiple comparison test and spectrophotometry to identify the main compounds present in EECAL. The results showed that for the group of animals treated with EECAL (500mg/kg), there was a significant reduction (p